AB0526 DIFFERENCES IN IMMUNOGLOBULIN LEVELS IN PATIENTS WITH ANCA-ASSOCIATED VASCULITIS AND RHEUMATOID ARTHRITIS TREATED WITH RITUXIMAB. (13th June 2020) - Sanz, M.; Bonilla, G.; Peiteado, D.; Benavent, D.; Plasencia, C.; Nuño, L.; Monjo, I.; Villalva, A.; Balsa, A.
Abstract : Background: Rituximab (RTX) is a chimeric monoclonal antibody against CD20 receptor, used in the treatment of rheumatic diseases. Hypogammaglobulinemia has been described as an adverse event. It has been reported that hypogammaglobulinemia is more frequent in patients with ANCA-associated vasculitis (AAV). Objectives: To study the basal characteristics of patients with AAV and rheumatoid arthritis (RA) in treatment with RTX and to analyze the risk factors of hypogammaglobulinemia. Methods: Retrospective observational study of patients treated with RTX. Patients diagnosed with AAV and RA with immunoglobulin levels prior to treatment and after each cycle were included. Clinical and demographic variables were analyzed. Both populations were compared using t-Student for continuous and chi-squared for categorical variables. The influence of the basal characteristics of the patients was analyzed using univariate and multivariate logistic regression models. Results: Among the 86 included patients, 10 (11.6%) had AAV and 76 (88.4%) RA. Patient's characteristics stratified by disease are included in Table 1 . The overall sample was divided into two groups, patients who developed hypogammaglobulinemia and patients who did not. Of the 12 patients who developed hypogammaglobulinemia, 4 had RA and 8 AAV (p<0.001). In the univariate analysis, patients who developed hypogammaglobulinemia presented higher age at diagnosis (61 ± 15 vs 43 ± 11 years, OR=1.14 p<0.001), shorter time of disease progression (4.9 ± 8 vs 12.6 ± 9 years, OR=0.86 p0.02) and lower gammaglobulin rates at baseline (744 ± 504 vs 1145 ± 295 OR=0.16 p0.006). There were more severe infections in the group of patients with hypogammaglobulinemia than in the group without it (1/4 [25%] vs 1/74 [1.4%], OR=0.42 p<0.001). Patients with hypogammaglobulinemia received a higher cumulative dose of steroids during treatment (OR=1, 000 p 0.019). Within the RA group, patients with hypogammaglobulinemia also received a higher cumulative dose of steroids (p 0.009). In the multivariate study, only age at the beginning of treatment (OR=1.1 p=0.020) remained a risk factor for the appearance of hypogammaglobulinemia. Conclusion: A significantly higher percentage of hypogammaglobulinemia is observed in patients with AAV treated with Rituximab, compared to patients with RA. The development of hypogammaglobulinemia seems to be influenced by age at diagnosis, years of disease progression, IgG levels prior to initiation of treatment and a higher cumulative dose of glucocorticoids (targeted in both the overall sample and the RA group). In addition, there is a higher frequency of severe infections in the hypogammaglobulinemia group. Studies with larger sample sizes are needed to confirm these results. Disclosure of Interests: María Sanz: None declared, Gemma Bonilla: None declared, Diana Peiteado: None declared, Diego Benavent: None declared, Chamaida Plasencia: None declared, Laura Nuño: None declared, Irene Monjo: None declared, Alejandro Villalva: None declared, Alejandro Balsa Grant/research support from: BMS, Roche, Consultant of: AbbVie, Gilead, Lilly, Pfizer, UCB, Sanofi, Sandoz, Speakers bureau: AbbVie, Lilly, Sanofi, Novartis, Pfizer, UCB, Roche, Nordic, Sandoz